Echolocation-related reversal of information flow in a cortical vocalization network - García-Rosales, Francisco; López-Jury, Luciana; González-Palomares, Eugenia; Wetekam, Johannes; Cabral-Calderín, Yuranny; Kiai, Ava; Kössl, Manfred; Hechavarría, Julio C. (Nature communications, 2022)
The mammalian frontal and auditory cortices are important for vocal behavior. Here, using local-field potential recordings, we demonstrate that the timing and spatial patterns of oscillations in the fronto-auditory network of vocalizing bats ( Carollia perspicillata ) predict the purpose of vocalization: echolocation or communication. Transfer entropy analyses revealed predominant top-down (frontal-to-auditory cortex) information flow during spontaneous activity and pre-vocal periods. The dynamics of information flow depend on the behavioral role of the vocalization and on the timing relative to vocal onset. We observed the emergence of predominant bottom-up (auditory-to-frontal) information transfer during the post-vocal period specific to echolocation pulse emission, leading to self-directed acoustic feedback. Electrical stimulation of frontal areas selectively enhanced responses to sounds in auditory cortex. These results reveal unique changes in information flow across sensory and frontal cortices, potentially driven by the purpose of the vocalization in a highly vocal mammalian model. How cortical areas interact during vocalization is not fully understood. Here the authors show that when bats vocalize, the behavioral function of emitted sounds determines the direction of information flow between frontal and auditory cortices.